2003
DOI: 10.1128/jb.185.20.6209-6214.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of divIVA and Other Genes Located in the Chromosomal Region Downstream of the dcw Cluster in Streptococcus pneumoniae

Abstract: We analyzed the chromosome region of Streptococcus pneumoniae located downstream of the division and cell wall (dcw) cluster that contains the homolog of the Bacillus subtilis cell division gene divIVA and some genes of unknown function. Inactivation of divIVA in S. pneumoniae resulted in severe growth inhibition and defects in cell shape, nucleoid segregation, and cell division. Inactivation of the ylm genes resulted in some morphological and/or division abnormalities, depending on the inactivated gene. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 26 publications
5
103
0
1
Order By: Relevance
“…33), the cell-division phenotype of mutants lacking functional StkP cannot be ascribed solely to the lack of phosphorylation of DivIVA, because a divIVA-null mutant shows a distinguishably different phenotype with rounder and unseparated cells instead of elongated cells (50). Preliminary studies based on the in vivo effects of DivIVA mutant derivatives in key amino acid residues that abolish phosphorylation and/or mimic constitutive phosphorylation agree with this interpretation.…”
Section: Discussionsupporting
confidence: 68%
“…33), the cell-division phenotype of mutants lacking functional StkP cannot be ascribed solely to the lack of phosphorylation of DivIVA, because a divIVA-null mutant shows a distinguishably different phenotype with rounder and unseparated cells instead of elongated cells (50). Preliminary studies based on the in vivo effects of DivIVA mutant derivatives in key amino acid residues that abolish phosphorylation and/or mimic constitutive phosphorylation agree with this interpretation.…”
Section: Discussionsupporting
confidence: 68%
“…6). 114 and are often present in plants and algae 61 , indicating that they might be involved in plastid division.…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%
“…Recently, several additional cell-division genes have been discovered in cyanobacteria. Some of these, including the ylm genes, are conserved throughout most bacteria 114 and are often present in plants and algae 61 , indicating that they might be involved in plastid division.…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Pinho & Errington (2004) reported that disruption of divIVA in Staphylococcus aureus did not have an effect on chromosome segregation or cell morphology. In contrast, inactivation of divIVA in S. pneumoniae resulted in severe growth inhibition, producing defects in cell shape, nucleoid segregation and cell division (Fadda et al, 2003). It was also revealed that S. pneumoniae divIVA is co-transcribed with other genes likely to be involved in cell division (Fadda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%